Milking the cow: Negotiating ownership of aid and policy in Rwanda - Rachel Hayman (University of Oxford, Global Economic Governance Programme (GEG), 2007)
Like many countries in sub-Saharan Africa, Rwanda is highly dependent upon flows of external assistance. The convergence of donors around Rwanda's poverty reduction strategy since the late 1990s, combined with international commitments to improve aid effectiveness, have both enhanced and hindered Rwandan "ownership" of policy processes. Rises in direct budget support and sectoral support have increased collaboration between government and donors in the preparation and implementation of policy. A complex aid management system has been established to coordinate this collaboration, over which the government has sought to assert more control. This gives a semblance of greater convergence between government and donor priorities, and aid to Rwanda is rising. However, the RPF-led government which has been in power since 1994 also has its own policy priorities which sometimes clash with donor perspectives. The government has held a steady line on issues such as internal and regional security, national unity, governance and economic development. Aid dependence does not prevent the government from forging its own path in the face of donor hesitancy. The handling of refugees, resettlement, justice, elections and regional security provide examples of areas where the government has pursued sometimes controversial policies. Some donors have frozen aid or scaled back programmes as a response. However, other donors have been supportive and aid flows overall have rarely suffered. This divergence amongst donors provides one avenue through which the government is able to negotiate policy space and enhance its ownership. Clever use of the moral authority gained from ending the genocide, the legacy of the genocide and international guilt, and the language of the prevailing norms of international development also enhances the RPF-led government's control over policy priorities wh ile ensuring a continuing supply of external assistance. The Rwandan case highlights the effects of an aid system which aims at increasing local ownership but which leads to heightened external entanglement in inte rnal policy processes, while at the same time demonstrating how an aid-dependent government can maintain policy autonomy.
Keywords: 330